Clinical and imaging predictors of intracerebral haemorrhage in stroke patients treated with intravenous tissue plasminogen activator. Issue 1 (16th December 2004) - Derex, L; Hermier, M; Adeleine, P; Pialat, J-B; Wiart, M; Berthezène, Y; Philippeau, F; Honnorat, J; Froment, J-C; Trouillas, P; Nighoghossian, N
Abstract : Objective: To evaluate clinical, biological, and pretreatment imaging variables for predictors of tissue plasminogen activator (tPA) related intracerebral haemorrhage (ICH) in stroke patients. Methods: 48 consecutive patients with hemispheric stroke were given intravenous tPA within seven hours of symptom onset, after computed tomography (CT) and magnetic resonance imaging (MRI) of the brain. Baseline diffusion weighted (DWI) and perfusion weighted (PWI) imaging volumes, time to peak, mean transit time, regional cerebral blood flow index, and regional cerebral blood volume were evaluated. The distribution of apparent diffusion coefficient (ADC) values was determined within each DWI lesion. Results: The symptomatic ICH rate was 8.3% (four of 48); the rate for any ICH was 43.8% (21 of 48). Univariate analysis showed that age, weight, history of hyperlipidaemia, baseline NIHSS score, glucose level, red blood cell count, and lacunar state on MRI were associated with ICH. However, mean 24 hour systolic blood pressure and a hyperdense artery sign on pretreatment CT were the only independent predictors of ICH. Patients with a hyperdense artery sign had larger pretreatment PWI and DWI lesion volumes and a higher NIHSS score. Analysis of the distribution of ADC values within DWI lesions showed that a greater percentage of pixels had lower ADCs (<400×10 −6 mm 2 /s) in patients who experienced ICH than in those who did not. Conclusion: Key clinical and biological variables, pretreatment CT signs, and MRI indices are associated with tPA related intracerebral haemorrhage.